Business letters and communications. - Elfenbein, Julien; Alexander Hamilton Institute (U.S.) (New York : Alexander Hamilton Institute, 1967)
This book clearly shows the reader how he can recognize good and bad writing and how he can edit his own work to make it effective. The chapter 1 contains the guidepost for effective business writing. It furthers talk about six directional guideposts discussed in this same chapter-the "you attitude", clarity, cohesiveness, conciseness, validity, and objectivity-are sufficiently important to deserve some treatment in depth.
Includes bibliographical references.
hza 02/08/2018
Loans
Keywords: Commercial correspondence